Long-Term Mentoring for Computer Science Researchers: Reaching out across computer science research communities. - Ringer, Talia; Ruppel, Emily; Sihang Liu; Garza, Elba; Sukyoung Ryu; Silva, Alexandra (Communications of the ACM, 2023)
The article looks at mentoring in the computer science fields of programming languages and computer architecture. The authors outline two volunteer-based multi-institution mentoring programs they were involved in creating, SIGPLAN-M and Computer Architecture Long-term Mentoring (CALM). Topics include how the programs recruit mentors and match them with mentees; how mentees say they have benefited from their relationships with mentors; and challenges they faced in setting up and administering the programs.